Hubungan Obesitas dengan Kadar Asam Urat Darah pada Mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sriwijaya - Soputra, Ezra Hans; Sinulingga, Sadakata; Subandrate, Subandrate (Sriwijaya Journal of Medicine, 2018)
Uric acid is the end product of purine catabolism which is sinthesized especially by the liver and excreted through urinary tract. Increased blood uric acid levels can cause many disease such as gout arthritis, hipertension, and renal disease. Individual with obesity often have lower renal excretion rate and may have increased production of uric acid. This study is conducted to determine the relationship of obesity and blood uric acid levels.This Study with cross-sectional design took a sample of 119 students of Medical Education Program Study at Medical Faculty of the Sriwijaya University by consecutive sampling. Body weight, body height, and uric acid levels then are taken using measurement tools appropriate, categorized, and processed according to research objectivesThe study found that 27,5% female and 10,3% male have hyperuricemia. A total of 39,3% obese students and 16,5% non-obese students have high level of uric acid. The result of bivariate analysis showed that there is a significant relationship between obesity and gender with blood uric acid levels (p=0,022 and 0,035 respectively). After multivariate analysis, factor that has relationship with uric acid level is obesity.Obesity have a significant relationship with uric acid levels.